THU0121 COMORBIDITIES AT DIAGNOSIS OF RHEUMATOID ARTHRITIS. (2nd June 2020) - Tidblad, L.; Westerlind, H.; Askling, J.; Saevarsdottir, S.
Abstract : Background: Although many studies have reported an increased burden of comorbidities in patients with rheumatoid arthritis (RA), and their impact on RA outcomes, few studies have compared the pattern of comorbidities already at diagnosis of RA, in relation to the burden among matched control subjects. Only such a comparison can inform on which comorbidities are increased already before RA diagnosis, presumably due to overlapping causal factors, and which arise as a consequence of the RA disease or its treatment. Objectives: The aim of this study was to investigate the pattern of common chronic conditions in patients with RA, overall and stratified by serological status, at the time of diagnosis, compared to a matched control group reflective of the general population. Methods: This nationwide study included patients with a new-onset RA diagnosis, using data from the Swedish Rheumatology Quality register, from 2006 to 2015. We included 11, 086 incident RA cases, of whom 62% were seropositive. From the Total Population Register, we identified 54, 813 population controls, individually matched on age, sex and county of residence. Information about registered comorbidity diagnoses during the five years up until the RA diagnosis was retrieved from the Swedish National Patient Register. Information on dispersed drugs during the year up until the RA diagnosis was collected from the Prescribed Drug Register. Comorbidity diagnoses were grouped into 10 different categories (see table 1 ). Logistic regression was used to compare comorbidities between cases and controls, adjusted for the matching variables. Results: In seropositive as well as in seronegative RA, comorbidities within the respiratory (OR 1.58, 95% CI 1.44-1.74), gastrointestinal (OR 1.17, 95% CI 1.08-1.27), infectious (OR 1.12, 95% CI 1.03-1.23), endocrine (OR 1.39, 95% CI 1.31-1.47) and neurological (OR 1.73, 95% CI 1.59-1.89) categories were more common already at the time of RA diagnosis, compared to the matched population controls, as outlined in table 1 . A history of cardiovascular disease was slightly increased among patients with seronegative RA (OR 1.20, 95% CI 1.07-1.36), and no increase was seen for non-cardiac vascular diseases. A history of psychiatric (OR 0.87, 95% CI 0.80-0.93) and cancer diagnoses (OR 0.81, 95% CI 0.71-0.93) was less common in seropositive RA vs. their matched controls. In terms of comorbidity burden, 15% of all RA patients had diagnoses from at least two of the ten comorbidity categories vs. 13% of the controls and 8% vs. 8% had diagnoses within three or more comorbidity categories. Conclusion: This large nationwide study demonstrates a marked increase in several comorbidities, in particular respiratory, endocrine and neurological diseases, already at, and before, the diagnosis of RA compared with age and sex matched controls, while psychiatric diagnoses are less common. These findings are important for the interpretation of comorbidity studies in established RA. Disclosure of Interests: Liselotte Tidblad: None declared, Helga Westerlind: None declared, Johan Askling Grant/research support from: JA acts or has acted as PI for agreements between Karolinska Institutet and the following entities, mainly in the context of the ARTIS national safety monitoring programme of immunomodulators in rheumatology: Abbvie, BMS, Eli Lilly, Merck, MSD, Pfizer, Roche, Samsung Bioepis, Sanofi, and UCB Pharma, Saedis Saevarsdottir Employee of: Part-time at deCODE Genetics/Amgen Inc, working on genetic research unrelated to this project